THE POLICY OF MULTICULTURALISM IN GERMANY: YESTERDAY AND TODAY - Irena Valerevna Lebedeva (Современная наука и инновации, 2022)
In article the author considers the attitude of accepting community to the migrants on an example of Germany as this country is one of the most actively accepting migrants, besides it has had the crisis of multi-culturalism some years ago and the today's problems are even more serious. The welcome-culture has become a new religion in modern Germany.